HAMBATAN PENDISTRIBUSIAN BERKAS REKAM MEDIS RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH dr. R. GOETENG TAROENADIBRATAPURBALINGGA BERDASARKAN ANALISIS USG (Urgency, Seriousness, Growth) - , EKSA MAULIDA RATNA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Medical records are the basic of data from all of components of the accreditation to be achieved, where the documentation of medical record has an important role in both the patient and the hospital. There are recognized that the information where obtained from medical records is a confidential. The information in the medical record is confidential because it describes about the special relationship between a patient with a doctor that must be protected in accordance with a medical ethics and legislation. In the Keputusan Menteri Kesehatan Republik Indonesia Nomor 377 of 2007 about Standar Profesi Perekam Medis dan Informasi Kesehatan, within the limits and scope of the second point states that create standards and guidelines for health information management includes the legal aspects of security elements (safety), confidentiality (confidential), security, privacy and data integrity. This research use a qualitative descriptive method and case study research design. The subjects of this research are medical records personnel, especially medical record officers who are on the filing, reporting and medical certificate in the Installation Medical Records, Medical Records Installation staff designated by the Chairman of the Working Group on Information and Communication Management (ICM). The objects of this research are the application of policies related to confidentiality, privacy, and integrity of the data then written policies related to confidentiality and privacy, written policies related to security and integrity of data. The data in this research collect by using an observation, documentation studies and interview. The application of the policy in Dr. Sardjito Hospital associated with 10 and 11 points to the ICM Working Group on confidentiality, privacy, security and data integrity is not maximized. There is still a medical officer who gave a copy of the medical record file contents should not be allowed to be copied to the patient. In the implementation of regulations in the field, there are still discrepancies.